2020
DOI: 10.1088/1742-6596/1477/4/042067
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hybrid Learning-Based Animation Media to Improve the Learning Outcomes of Multimedia Learning

Abstract: This research aims to determine student learning outcomes and produce animated learning based on hybrid learning. In this case, the type of research is research and development (R&D) with 4D models with stages namely potential or problems, data collection, product design, design validation, design revisions, product testing, product revision, practical utility testing and revision of the final product. The sample data were recorded in the Faculty of Economics, Universitas Negeri Medan. The result of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…Animation video-based are media that can increase student motivation in participating in distance learning (Rachmavita, 2020). Besides being able to support distance learning, through the use of animation video-based, learning outcomes will increase (Simarmata, 2020). The results of previous studies revealed that effective distance learning practices can be influenced by one thing, namely the use of media (Macinko, 2020).…”
Section: Figure 4 An Assessment Of Media Feasibility By Studentsmentioning
confidence: 99%
“…Animation video-based are media that can increase student motivation in participating in distance learning (Rachmavita, 2020). Besides being able to support distance learning, through the use of animation video-based, learning outcomes will increase (Simarmata, 2020). The results of previous studies revealed that effective distance learning practices can be influenced by one thing, namely the use of media (Macinko, 2020).…”
Section: Figure 4 An Assessment Of Media Feasibility By Studentsmentioning
confidence: 99%
“…4-D is a development model of research and development procedures. According to Trianto in [12] 4-D consists of 1) Define, 2) Design, 3) Develop, and 4) Disseminate. However, this research is limited to the third step-3D, which is the develop stage only.…”
Section: Methodsmentioning
confidence: 99%
“…Using animated video-based instruction can not only improve learning results but also facilitate remote learning (Simarmata, 2020). Previous research has shown that one factor, namely media consumption, may affect successful distant learning practices (Macinko, 2020).…”
Section: Benefits Of Distance Learning Through Animationmentioning
confidence: 99%